Unlocking financial inclusion: Indian banks' efficiency in Pradhan Mantri Jan-Dhan Yojana explored through DEA - Ajay Pal Singh; Gagan Deep (Rajagiri Management Journal)
Purpose – Financial inclusion is a prerequisite for inclusive development. In 2014, the Indian Government introduced the Pradhan Mantri Jan-Dhan Yojana (PMJDY) with a similar objective. The study aims to analyse the effectiveness of banks in the implementation of financial inclusion policy, i.e. PMJDY. Design/methodology/approach – To evaluate the effectiveness of Indian banks, the study used the data over a seven-year period, from 2014–2015 to 2020–2021. Data are analysed by using the data envelopment analysis technique. Findings – The study discovered that public sector banks performed better than private sector banks (PVBs) in terms of boosting financial inclusion under the PMJDY scheme. In terms of implementing the PMJDY programme, the State Bank of India rated first. Practical implications – Results recommended that policymakers set goals for banks. In order to encourage consumers to utilise their accounts, banks ought to introduce supplementary financial products and implement incentive programs. Originality/value – The study is the first of its kind to measure the performance of Indian banks in the implementation of the PMJDY scheme.